2006
DOI: 10.1016/j.foreco.2006.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Changes in understory vegetation of a ponderosa pine forest in northern Arizona 30 years after a wildfire

Abstract: Wildland fires can cause shifts in understory species composition and production. Many studies have examined short-term changes in understory vegetation following a wildfire; however, very few long-term studies are available. The objective of this study was to examine changes in understory (herbaceous and shrub) species composition and production since the 1972 Rattle Burn wildfire on the Coconino National Forest near Flagstaff, Arizona. Understory species composition and production were originally sampled in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 32 publications
4
41
0
Order By: Relevance
“…5,6). This is consistent with Bataineh et al (2006), who found that even in lightly burned areas, removal of forest canopy or litter stimulated understorey vegetation growth for more than a decade following a wildfire in Arizona. While soil and char cover decreased consistently over time, NPV and understorey GV increased; the rates of increase varied depending on the initial burn severity condition (Figs.…”
Section: Vegetation Recovery Was Rapid Regardless Of Burn Severity CLsupporting
confidence: 90%
“…5,6). This is consistent with Bataineh et al (2006), who found that even in lightly burned areas, removal of forest canopy or litter stimulated understorey vegetation growth for more than a decade following a wildfire in Arizona. While soil and char cover decreased consistently over time, NPV and understorey GV increased; the rates of increase varied depending on the initial burn severity condition (Figs.…”
Section: Vegetation Recovery Was Rapid Regardless Of Burn Severity CLsupporting
confidence: 90%
“…During dry conditions, litter on the ground serves as fuel which can increase the risk of forest fires, a disturbance commonly structuring stands of Pc (Sibold et al, 2007). More fires would have extensive effects on stand as well as landscape levels but are likely to pave the way for denser understorey vegetation (Bataineh et al, 2006) and a more pristine understorey flora (Laughlin et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In P. ponderosa Dougl. (ponderosa pine) forest perennial grass cover decreased and invasive species increased as fire intensity and litter consumption increased (Armour et al 1984;Griffis et al 2001;Bataineh et al 2006;Sabo et al 2009). …”
Section: Herbaceous and Ground Cover Responsementioning
confidence: 99%